Perancangan UI/UX Pada Sistem Perpustakaan dengan Pendekatan Design Thinking - Salam, Muhammad Ifsyaus; Setiawan, Agus; Sukmasetya, Pristi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The library serves as a literacy center for students, where it is expected to have adequate facilities and infrastructure for visitors. In the current digital era, the management and recording no longer rely on handwritten books, leading to discrepancies in bookkeeping and other records. The web-based library system at MTs Negeri 3 Magelang was initially created to assist librarians in addressing challenges and issues arising from manual recording. However, the features of the system have not fully optimized user needs. Therefore, a thorough evaluation is needed to identify user needs related to recording. In response, a redesign was carried out using the design thinking method to better meet the needs of users for the Library System at MTs Negeri 3 Magelang. The results of usability testing using the Single Ease Question (SEQ) method, with an average ranging from 6.5 to 7, indicate that the prototype of the Library System at MTs Negeri 3 Magelang has achieved a good level of effectiveness, efficiency, and user satisfaction.